Comparación del efecto de riego con aguas residuales provenientes de las lagunas de oxidación de Santa Elena, sobre 4 especies forestales (loxopterygium huasango,tabebuia sp, pseudosamanea guachapele,caesalpinia glabrata) en etapa de vivero - Noboa León, Maria Elena (2011)
The present research shows the comparison between the uses of oxidation ponds in “El Canton Santa Elena” to be used later in the irrigation of forestry species. Loxopterygium huasango, Tabebuia sp., Pseudosomanea guachapele, and Caesalpinia glabrata, in order to find the treatment with best results. The data used for the experimentation was: survivor, high in plant, number of leaves and stem diameter, doing the procedure every week for three months. The result of the treatment consists in the use of water obtained from the facultative pond, maturation and potable water, interacting with four forestry species of Santa Elena. The experimental context was done by the design of split pots being the main factor: forestry species, and its sub factors: types of water. The data obtained analyzed from the experimental units by ADEVA determinate that there is not significance difference between the treatments, it means that this species could be used for irrigation with water coming from the oxidation ponds during the nursery phase